PENGARUH STRUKTUR KEPEMILIKAN PUBLIK, PRAKTIK PENGELOLAAN PERUSAHAAN, JENIS INDUSTRI, UKURAN PERUSAHAAN, PROFITABILITAS DAN RISIKO KEUANGAN TERHADAP TINDAKAN PERATAAN LABA (STUDI EMPIRIS PADA INDUSTRI YANG LISTING DI BURSA EFEK JAKARTA) - Herni Herni; Yulius Kurnia Susanto (Journal of Indonesian Economy and Business (JIEB), 2008)
This research is designed to examine the influence of company’s characteristics on income smoothing action among listing companies at Jakarta Stock Exchange. The factors being examined were public ownership structure, corporate governance practice, industrial type, firm size, profitability and financial risk. Corporate governance practice namely audit quality, independent commissioner board and audit committee. Eighty one listed companies at Jakarta Stock Exchange selected using purposive sampling method were used as research sample, with period from 2002 until 2006. The sample was classified into smoother and non smoother using Eckel’s model. Data were analyzed using binary logistic regression. The results of the analysis indicated that public ownership structure, corporate governance practice, industrial type, firm size, profitability had a significant influence on income smoothing action and the influence of financial risk on income smoothing action was not significant.